Análisis del impacto del marketing emocional de Taylor Swift en redes sociales en la audiencia ecuatoriana: evaluación del contenido emocional en las publicaciones de Instagram y TikTok durante el periodo de junio a agosto de 2023 - Jaramillo Peñarreta, Daniela Fernanda (2024)
The objective of this research is to analyze the impact of Taylor Swift's emotional marketing in her Instagram and TikTok publications during the period from June to August 2023 in the Loja canton, this allowed to identify, analyze and conclude that the implementation of emotions and certain elements are fundamental for the success of a brand, additionally, it is observed that these characteristics achieve audience loyalty. The methodology used was exploratory and descriptive, and additionally, it was carried out under a mixed approach, with their respective instruments: Observation tables and survey. As a result, it was identified that the posts made during the three months of research, make use of elements such as: trust, honesty, understandable language, brand image, design and personalization, which were recognized through variables and sub-variables of the Value Star model. Among the conclusions is that the publications that attract and generate more impact on Ecuadorian followers are the announcements of new musical projects and additionally, in which Swift shows her more personal side, managing to generate positive emotions in users, these were classified as positive and negative, thanks to the help of Robert Plutchik's Wheel of Emotions. Keywords: Emotional marketing; Taylor Swift; Instagram; TikTok; Value Star model; wheel of emotion